Assessment of the cytotoxic effects and chemical composition of the insoluble precipitate formed from sodium hypochlorite and chlorhexidine gluconate. (1st July 2021) - Jeong, Ji Wook; Sarmast, Nima D.; Terlier, Tanguy; van der Hoeven, Ransome; Holland, Julian N.; Parikh, Neha
Abstract: Aim: To investigate (1) the cytotoxic potential of the brown precipitate (BP) formed with sodium hypochlorite (NaOCl) and chlorhexidine gluconate (CHX), using both a small animal model of Caenorhabditis elegans ( C .  elegans) and cultured human gingival fibroblasts; and (2) the chemical composition of BP using Time‐of‐Flight Secondary Ion Mass Spectrometry (ToF‐SIMS). Methodology: Brown precipitate was obtained by mixing equal volumes of 6% NaOCl and 2% CHX and separating the BP from clear supernatant by centrifugation. The brown precipitate was weighed and solubilized in dimethyl sulfoxide for cytotoxicity experiments. The cytotoxic effect of BP was assessed using C .  elegans larvae and primary immortalized human gingival fibroblasts‐hTERT (hTERT‐hNOF) cells. Various dilutions of BP (25 ng/µL–150 ng/µL), supernatant (0.15% v/v), NaOCl (1:100–1:1000 dilutions of 6% NaOCl) or CHX (1:500–1:1000 dilutions of 2% CHX) along with vehicle control (0.5% v/v ethanol and 0.15% v/v DMSO) or untreated control (growth medium) were tested on C .  elegans larvae and hTERT‐hNOF cells. Viability was assessed in C .  elegans larvae using stereomicroscopy and in hTERT‐hNOF cells using dehydrogenase‐based colorimetric assay. ToF‐SIMS was used to assess the chemical composition of BP in comparison with CHX and para‐chloroaniline (PCA). The C .  elegans and cell line data were analysed using Log‐Rank test and Student's t‐test, respectively ( p  < .05). Results: BP‐75 ng/µL and BP‐150 ng/µL were significantly more toxic to C .  elegans larvae than the untreated, vehicle, supernatant or CHX treatment groups ( p  < .0001). Similarly, in hTERT‐hNOF cells, BP‐50 ng/µL, BP‐75 ng/µL and BP‐150 ng/µL induced significant cytotoxicity within 2 h compared with untreated, vehicle, supernatant and CHX treatments ( p  < .05). ToF‐SIMS analysis of BP revealed ion composition characteristic of both CHX and the carcinogen PCA. Conclusions: Brown precipitate was toxic in both C .  elegans larvae and hTERT‐hNOF cells. The ToF‐SIMS analysis of BP revealed ions characteristic of CHX and PCA that could account for the toxicities observed in C .  elegans larvae and human gingival fibroblasts. Because of the insoluble and toxic nature of BP, consecutive use of CHX and NaOCl irrigants should be avoided in root canal treatment.